Hubungan Prilaku Sleep Hygiene Dengan Kualitas Tidur Remaja Usia 10-19 Tahun Di RW06 Desa Cirimekar Kecamatan Cibinong Tahun 2023 - Sadam Hafidz Fakhrurrozi; Rina Afrina; Nining Rukiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Sleep hygiene is placing the most comfortable position to sleep soundly every night by optimizing your sleep schedule. Sleep quality is defined as an individual's satisfaction with the sleep experience. Sleep quality has four attributes, namely sleep efficiency, sleep latency, sleep duration and awakening after sleep onset. According to WHO, the age limit for teenagers is 10 to 19 years. From this research, to determine the relationship between sleep hygiene behavior and the sleep quality of adolescents aged 10-19 years in RW 06 Cirimekar Village, Cibinong District. The population and sample in this study consisted of 87 teenage respondents. This research design uses a cross sectional approach. Data collection used the Index Sleep Hygiene (ISH) questionnaire to measure sleep hygiene, then the Pitsburg Sleep Quality Index (PSQI) questionnaire to measure sleep quality. In this study, entitled The Relationship between Sleep Hygiene Behavior and Sleep Quality in Adolescents Aged 10-19 Years in RW 06 Cirimekar Village, Cibinong District, the results of measuring sleep hygiene and sleep quality were obtained using the chi square statistical test results, with a p-value of 0.04 (p -value < 0.05) so it can be concluded that there is a significant relationship between sleep hygiene behavior and adolescent sleep quality.